Phase decomposition and strengthening in HfNbTaTiZr high entropy alloy from first-principles calculations. (15th February 2022) - Chen, Shu-Ming; Ma, Ze-Jun; Qiu, Shi; Zhang, Lian-Ji; Zhang, Shang-Zhou; Yang, Rui; Hu, Qing-Miao
Abstract: Phase decomposition influences significantly the mechanical properties of high entropy alloys (HEAs). Prediction of the phase decomposition of HEA is greatly hindered by the hyper-dimensional composition space of the alloys. In the present work, we propose to represent the HEAs as various pseudo-binary alloys of which the temperature dependent free energies as functions of compositions may be readily calculated by using first-principles methods in combination with thermodynamic models. With the calculated free energies, the phase diagrams of the pseudo-binary alloys may be constructed and the phase decomposition can be predicted. This procedure is applied to Hf-Nb-Ta-Ti-Zr alloy with body-centered cubic (BCC) structure. We predict that the equiatomic HfNbTaTiZr HEA suffers from phase decomposition below critical temperature of 1298 K. The HEA decomposes most favorably to BCC NbTa-rich and HfZr-rich phases. The BCC HfZr-rich phase transfers to a hexagonal close-packed structure (HCP) phase at low temperature. The predicted compositions of the decomposed phases are in good agreement with experiment and Thermal-Calc modeling. Furthermore, the effect of the phase decomposition on the strength of the HEA is evaluated by considering the solid-solution and precipitation strengthening mechanisms. The precipitation strengthening effect is stronger than the solid-solution strengthening at the low annealing temperature but becomes weaker at high annealing temperature. Graphical abstract: Image, graphical abstract .